Grizzled Mantid (suggested common name) Gonatista grisea (Fabricius) (Mantodea: Mantidae) - Haleigh A. Ray; Jennifer L. Gillett-Kaufman (EDIS)
The grizzled mantid, Gonatista grisea (Fabricius) (Figure 1), is an arboreal (tree dwelling) mantid commonly found in Florida. It is a mottled gray-green in color and somewhat flattened, which allows it to mimic lichens while pressed against tree trunks (Krombein 1963). Grizzled mantids are predators of other arthropods. [...]